Fortification of edible zein films with thyme, laurel and orange essential oils and determination of their antifungal and radical scavenging properties - Gucbilmez, Cigdem Mecitoglu; Oksuz, Omer; Arici, Muhammet (M H SCHAPER GMBH CO KG, 2019)
The purposes of this research were: (a) to produce zein films by adding certain essential oils (EOs), (b) to identify their antifungal activity on some yeasts and molds, and (c) to develop an edible zein film that can inhibit the growth of Aspergillus fumigatus which was identified in a previous study as the most heat resistant mold isolated from margarines. Zein films fortified with thyme (Thymus vulgaris), laurel (Laurus nobilis) and orange (Citrus sinensis) EO were tested for their antifungal activities against 3 molds and 5 yeasts by measuring inhibition zone diameters. Considering the single effect, thyme EO was determined as the most effective one. Furthermore, the antifungal activities of thyme EO combined with the other EOs were also studied. From the obtained data, films containing thyme EO in combination with laurel EO were found as the most effective against Aspergillus fumigatus. Then, minimally inhibitory concentration against Aspergillus fumigatus was determined for the zein film obtained from film solutions including only thyme EO as 1.7 % (v/w), combinations of thyme-laurel EO as 1.6 % (v/w). Also, thyme oil was found as EO having the highest radical scavenging activity and total phenolic compounds among the three EOs.
Keywords: Antifungal activity; Radical scavenging activity; Essential oil; Zein film; Thymus vulgaris; ANTIOXIDANT ACTIVITY; PACKAGING TECHNOLOGIES; EXTRACTS; FRACTIONS; VULGARIS; COATINGS; GROWTH; Chemistry; Food Science & Technology; Toxicology